Domestication-selected COG4-OsbZIP23 module regulates chilling tolerance in rice - Shenli Sun; Dongfeng Liu; Wei Luo; Zhitao Li; Jinglei Feng; Yalong Guo; Kang Chong; Yunyuan Xu (Cell Reports)
Summary: Identifying excellent natural variations is the foundation for breeding. Several major genes of quantitative trait loci for chilling tolerance at the seedling stage (qCTS) have been identified. However, less is known about the dual elite modules for the tolerance. Here, we report the major gene of qCTS1-2, Chilling-tolerance in Geng/japonica rice 4 (COG4), encoding the transcription factor ENAC1, coupled with OsbZIP23 to positively regulate chilling tolerance. The haplotype analysis and geographical distribution show that most of the chilling-tolerant japonica varieties carry Var9(CT) at −317 in COG4 (COG4jap). The COG4jap promoter is preferentially bound by cold-induced OsbZIP23 to cause a higher expression of COG4jap compared to COG4ind, which promotes multiple pathways for the tolerance. Both COG4jap and OsbZIP23jap are artificially selected and retained in japonica varieties during domestication. These results not only reveal the regulatory mechanism of OsbZIP23jap-COG4jap module but also provide valuable variations for molecular design breeding.